New species of the genus Macrogynoplax and new records of Anacroneuria (Plecoptera: Perlidae) from Roraima State, Brazil - Menezes, Emely Trajano De; Boldrini, Rafael; Novaes, Marcos Carneiro (Zootaxa, 2020)
Adults of Plecoptera of the family Perlidae were studied from seven municipalities of Roraima State, Brazil. One new species of Macrogynoplax Enderlein, 1909 was discovered and is described. We also report seven species of Anacroneuria Klapálek 1909 that represent two new country records for Brazil, A. caraca Stark, 1995 and A. cruza Stark, 1995, and five species, A. atrifrons Klapálek, 1922, A. blanca Stark, 1995, A. minuta Klapálek 1922, A. marlieri Froehlich 2001 and A. pictipes Klapálek 1923 that are new records for Roraima State. Additionally, we reported variant specimens of A. marlieri and A. minuta.